Women’s advocacy for imposing stringent stipulations on polygamy in muslim marriage and divorce act of Sri Lanka: a juristic analysis - Fowzul, Mohamed Buhary; Haneef, Sayed Sikandar Shah (Zes Rokman Resources, 2020)
There has been a deadlock between the women’s organizations and the Islamic jurists concerning the reforms in Muslim Marriage and Divorce Act of Sri Lanka. Exclusively, the women organizations in Sri Lanka advocate for reforming the polygamous system by imposing harsh conditions on the husbands who intend to contract subsequent marriages such as obtaining the consent of the first wife, assurance of fair treatment, declaration of assets and nullification of the marriage if it is not registered officially. All these changes are lobbied for the ultimate purpose of gradual abolition of polygamy so as to safeguard the women and children from the detrimental effects of polygamy physically, fiscally, mentally and socially. Nonetheless, the Islamic jurists in Sri Lanka denounce this proposal as being fallacious and against the ruling of polygamy in Islam. Hence, this study aims to bridge the gaps by breaking the deadlock between the women organizations and the Islamic jurists. Accordingly, it crutinizes the women’s lobby for amending the polygamous practice and its contingencies in the Sri Lankan context by juristic analysis drawing on the Islamic jurisprudential sources, the standpoints of prominent jurists and the outlook of eminent scholars in Sri Lanka from both parties as obtained from interviews. Consequently, the outcome of this study provides a mediating solution for breaking the thirty years’ long-lasting deadlock considering the interests and aspirations of not only women one-sidedly but those of men and children as well.